Mediação da literatura : contação de história pelo Youtube - Pereira, Anelise Boaventura (My University, 2024)
The way storytelling happens changes over time. Even though gestures and voice are vehicles for telling stories, the ways and means of telling are changing with the intention of reaching those who are not physically close to the teller. Therefore, the following statement is chosen as the research problem: how does literary reading mediation occur on YouTube? For this reason, this dissertation has the general objective of investigating the storytelling on YouTube channels by two storytellers, in order to contribute to studies on cultural mediation through technology. And, as specific objectives, discuss the concept of literary reading mediation; describe, based on episodic interviews, information about the personal and professional career of the tellers; and analyze differences and similarities in the way the tellers present the narratives to the viewer.The theoretical foundation of this research is based on Hauser (1977), Petit (2019), Yunes and Oswald (2003), Zilberman (1991), Castrillón (2011), Neitzel and Ramos (2022), Goulart and Ferreira (2022) in which concerns the mediation of literary reading; in Candido (2011), Benjamin (1987), Zilberman (2003, 2008), Ramos (2010), Ramos and Panozzo (2015) to deal with literature, narrative and literature for children; and in Yunes (2012), Busatto (2012, 2013), Abramovich (2006) and Bajard (1994) to address storytelling. Regarding the methodological aspect, this study is based on Bauer and Gaskell (2002) and Flick (2004, 2015). The research is qualitative in nature, with a descriptive approach, and is based on bibliographical study and episodic interviews as an instrument for contextualizing the work of two storytellers, namely: Milene Barazzetti and Rosane Castro.In addition to the interviews, five story-telling videos from each teller, broadcast on YouTube, are described and analyzed, considering elements such as costumes, scenery, connection with the viewer, performance in the telling, recording characteristics, among other aspects. As results, particularities are highlighted regarding the continued training of storytellers and singularities are pointed out about the way in which they tell the chosen stories to viewers. [resumo fornecido pelo autor]
O modo como a contação de histórias acontece vai se modificando com o passar dos tempos. Mesmo que gestos e voz sejam veículos para narrar histórias, os modos e os meios de contar vão se alterando com a intenção de chegar também para aqueles que não estão próximos fisicamente do contador. Assim, elege-se como problema da investigação o seguinte enunciado: como ocorre a mediação de leitura literária no Youtube? Diante disso, esta dissertação tem como objetivo geral investigar a contação de histórias em canais do Youtube de duas contadoras, a fim de contribuir para os estudos sobre a mediação cultural por meio da tecnologia. E, como objetivos específicos, discutir o conceito de mediação de leitura literária; descrever, a partir de entrevista episódica, informações sobre o percurso pessoal e profissional das contadoras; e analisar diferenças e semelhanças no modo como as contadoras apresentam as narrativas ao espectador. A fundamentação teórica desta pesquisa apoia-se em Hauser (1977), Petit (2019), Yunes e Oswald (2003), Zilberman (1991), Castrillón (2011), Neitzel e Ramos (2022), Goulart e Ferreira (2022) no que diz respeito à mediação de leitura literária; em Candido (2011), Benjamin (1987), Zilberman (2003, 2008), Ramos (2010), Ramos e Panozzo (2015) para tratar de literatura, narrativa e literatura para infância; e em Yunes (2012), Busatto (2012, 2013), Abramovich (2006) e Bajard (1994) para abordar contação de história. Quanto ao aspecto metodológico, este estudo ampara-se em Bauer e Gaskell (2002) e em Flick (2004, 2015). A pesquisa é de caráter qualitativo, com abordagem descritiva, e pauta-se em estudo bibliográfico e na realização de entrevista episódica como instrumento para a contextualização da atuação de duas contadoras de histórias, a saber: Milene Barazzetti e Rosane Castro. Além das entrevistas, cinco vídeos de contação de história de cada contadora, veiculados no Youtube, são descritos e analisados, considerando elementos como figurino, cenário, conexão com o espectador, atuação na contação, características da gravação entre outros aspectos. Como resultados, evidenciam-se particularidades acerca da formação continuada das contadoras de histórias e apontam-se singularidades sobre o modo como elas transmitem aos espectadores as histórias escolhidas. [resumo fornecido pelo autor]
Keywords: Contadores de histórias; Pandemias; YouTube (Recurso eletrônico); Story tellers; Pandemics; YouTube Broadcast Yourself (Electronic resource)